Conhecimentos revelados por tutores em um curso de formação continuada para professores de Matemática na modalidade a distância - Esquincalha, Agnaldo da Conceição (2015)
This work aims at investigating the knowledge revealed by tutors of a distance continuing education course for mathematics teachers. The context of the research was the tutoring system of the Improvement Course in Mathematics, offered by the State Government of Rio de Janeiro from 2011 onwards. Initially we follow the work of 32 tutors over a year between 2011 and 2012 in order to list and classify the types of interventions in discussion forums among the course participants. After considering the results, we offer initial training to freshman tutors in 2012, to promote an improvement in the actions that we consider to be below expectations. Between August 2012 and July 2013 six tutors, the subjects of this research, were followed and participated in a training program in service. For the training of tutors, beyond the specifics of the Improvement Course in Mathematics, we grounded our work on the TPACK (Technological Pedagogical Content Knowledge) theoretical framework, assuming that technological, pedagogical and mathematical knowledge skills are fundamental for the exercise of their functions. The research, qualitative in nature, made use of questionnaires and conducting focus groups to collect data, which were interpreted under the light of thematic content analysis. For the triangulation of data, we used the discursive types found in interventions by tutors in the course s discussion forums. Our analysis indicated that affective and attitudinal components play a key role in the exercise of mentoring in this context and, therefore, we concluded the research by proposing the expansion of TPACK theoretical framework, including these components in a fourth type of knowledge, featuring TPACK-OTE (Technological Pedagogical Content Knowledge-Online Teacher Education)